Development of a conceptual framework to detect perioperative symptom burden following abdominal surgery for cancer - Birgin, Emrullah; Müller, Mitho; Woll, Christian; Klompmaker, Annika; Téoule, Patrick; Reißfelder, Christoph; Rahbari, Nuh Nabi (European journal of surgical oncology, 2023)
Background: Abdominal surgery for gastrointestinal malignancies has a signiﬁcant impact on patients' health-related quality of life. However, there is so far no patient-reported outcome measures (PROM) in the immediate postoperative period to detect the perioperative symptom burden and patients’ needs which may precede occult and severe complications. The aim of the study was to create a conceptual framework for the development of a PROM to measure perioperative symptom burden in abdominal cancer patients. - Methods: This mixed method study was performed between March 2021, and July 2021 as part of a multiphase approach to develop a new PROM. A systematic review of the literature was performed health domains were identiﬁed. The relevance of the health domains was assessed in a two-round Delphi study with clinical experts. Qualitative interviews were performed in patients who underwent abdominal surgery for cancer. - Results: The systematic literature review yielded 12 different PROM with 168 items and 55 health domains. The most common health domains involved the “digestive system” and “pain”. In total, 30 patients (median age 66 years, 20 men [60%]) were included for qualitative patient interviews. Of 16 health domains identiﬁed by the Delphi study, a total 15 health domains were conﬁrmed during patients’ interviews. The ﬁnal conceptual framework included 20 health domains. - Conclusion: This study provides the essential groundwork to develop and validate a new PROM for the immediate postoperative period of patients undergoing abdominal surgery for cancer. © 2023 Elsevier Ltd, BASO ~ The Association for Cancer Surgery, and the European Society of Surgical Oncology. All rights reserved.